THE SAGA OF FOOD SECURITY IN WEST BENGAL - Basu, Ranjan (International Journal of Research -GRANTHAALAYAH, 2020)
Undivided Bengal in India was struck by series of famines during the pre-colonial and colonial periods. In post partition era though there is no record of famine, starvation and malnutrition are not unknown in West Bengal among the people lying below the poverty line. Lacunae in the public distribution system might be one major hurdle. Implementation of several welfare programs and National Food Security Act, 2013 seems to be conducive to control the menace of starvation. But the concept of food security has been deduced to food grain security only without any provision of protein, minerals and vitamins, the essential ingredients of nutrition. Nutrition of mothers, children and senior citizens along with male bias of nutrition—all are in question now. Throughout India while farmers are living in debt from hand to mouth, agriculture is no more a lucrative occupation. Several measures have been introduced to combat such a disastrous situation viz. efficient storage and marketing system, loan waiver, bank transfer of grant-in-aid, minimum support price and efficient public distribution system, apart from targeted nutrition schemes. But no one can be considered as effective action so far to break the ice.